2011
DOI: 10.1007/s12088-011-0119-0
|View full text |Cite
|
Sign up to set email alerts
|

Autohydrolysed Tilapia nilotica Fish Viscera as a Peptone Source in Bacteriocin Production

Abstract: Fish processing generates large amounts of solid and liquid wastes. Many different by-products have been produced from fish processing wastes. Studies on solubilization of Bolti fish (Tilapia nilotica) viscera by endogenous enzymes at different pHs are described. Hydrolysis reactions were conducted with freshly thawed viscera utilizing an initial temperature gradient and terminated at various time points by heat inactivation of the enzymes. Various peptones obtained from hydrolysed visceral homogenates of Bolt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
13
0
5
Order By: Relevance
“…The fish processing industry generates large quantity of liquid and solid wastes, and due to their high protein content, they have been proposed as alternative for preparation of valuable products (Kim & Wijesekara, ; Ferraro et al., ; Rustad, Storrø, & Slizyte, ). Peptones obtained from fish‐processing waste have demonstrated that can produce high amounts of bacteriocins from L. sakei Lb 706 (Deraz, El‐Fawal, Abd‐Ellatif, & Khalil, ), up to 500% more than the quantity obtained using commercial media. Also using peptone derived from fish waste products have demonstrated to support LAB growth and metabolic necessities (Vázquez, Docasal, Prieto, González, & Murado, ), with better results than the gold standard media (MRS; Safari et al., ).…”
Section: Selection Of the Protein‐based Mediamentioning
confidence: 99%
“…The fish processing industry generates large quantity of liquid and solid wastes, and due to their high protein content, they have been proposed as alternative for preparation of valuable products (Kim & Wijesekara, ; Ferraro et al., ; Rustad, Storrø, & Slizyte, ). Peptones obtained from fish‐processing waste have demonstrated that can produce high amounts of bacteriocins from L. sakei Lb 706 (Deraz, El‐Fawal, Abd‐Ellatif, & Khalil, ), up to 500% more than the quantity obtained using commercial media. Also using peptone derived from fish waste products have demonstrated to support LAB growth and metabolic necessities (Vázquez, Docasal, Prieto, González, & Murado, ), with better results than the gold standard media (MRS; Safari et al., ).…”
Section: Selection Of the Protein‐based Mediamentioning
confidence: 99%
“…A previous study comparing several peptones from different origins, denominations and commercial brands led to a wide range of productive yields for the formation of bacteriocins and the growth of lactic acid bacteria [35]. In this context, protein substrates extracted from tuna heads and cod or tilapia viscera with varying degrees of hydrolysis have been reported as fundamental ingredients for complex media [14,37,38].…”
Section: Growth Of Lactic Acid Bacteria On Peptones From Pensmentioning
confidence: 99%
“…Moreover, Poernomo and Buckle (2002) reported that peptone isolated from cowtail ray (Trygon sephen) viscera was able to support the microbial growth rate of Bacillus subtilis, Escherichia coli, Staphylococcus aureus and Saccharomyces cerevisiae cultures. Deraz et al (2011) used tilapia viscera for peptone production and showed a high biomass production. Srikandace et al (2017) reported that peptone extracted from kerong fish (Terapon jarbua) showed a higher growth rate in E. coli compared to commercial peptone.…”
Section: Introductionmentioning
confidence: 99%